Reflection : principles and practices for heathcare professionals - Ghaye, Tony; Lillyman, Sue (Reflective practices series., 2010)
In this newly updated edition of the bestselling Reflections: Principles and Practice for Healthcare Professionals, the authors reinforce the need to invest in the development of reflective practice, not only for practitioners, but also for healthcare students. The book discusses the need for skilful facilitation, high quality mentoring and the necessity for good support networks. The book describes the 12 principles of reflection and the many ways it can be facilitated. It attempts to suppo ...